(untitled) (Journal of Plant Disease Sciences, 2023)
The seeds of susceptible soybean cultivar TAMS-38 were used for studying the pathogenicity of isolate in sick pot culture. In the pathogenicity test, R. bataticola found pathogenic to soybean causing 80% root rot disease. The soybean TAMS-38 exhibited root rot on 30-35 days after sowing. Poisoned food technique was employed to test the efficacy of fungicides viz. Carbendazim, Thiram, Captan, Carboxin, Mancozeb, Metalaxyl + Mancozeb, and Copper oxychloride against R. bataticola in vitro. The most effective fungicides in arresting (100%) mycelial growth were Carbendazim (0.1%), Carboxin (0.1%), Mancozeb (0.25%), Metalaxyl + Mancozeb (0.2%) and Copper oxychloride (0.3%), whereas the minimum mycelial growth inhibition was recorded by Captan and Thiram.